Cesarean Scar Pregnancy and Successful Ultrasound-Guided Removal after Uterine Artery Ligation - Vito Leanza; Giosuè Giordano Incognito; Ferdinando Antonio Gulino; Attilio Tuscano; Monia Cimino; Marco Palumbo (Case Reports in Obstetrics and Gynecology)
A correct management of cesarean scar pregnancy (CSP) is mandatory to avoid further complications. There is no consensus for the standard therapy and the most frequent methods used are not free from failures and sequelae. A 38-year-old woman was admitted referring amenorrhea lasting 9 weeks, pelvic pain, and vaginal bleeding. She had three previous cesarean sections. Transvaginal ultrasound showed a gestational sac of 16 mm in the cervico-isthmic site and inside the thickness of the uterine wall, and the dosage of beta-human chorionic gonadotropin was 12,770 mU/mL. A diagnosis of CSP was done, and an ultrasound-guided removal after uterine artery cervical branch ligation was performed. The follow-up was uneventful. Even if not yet codified in the literature, our therapeutic procedure should be considered in other similar cases in the future, as it potentially limits the possible iatrogenic problems and reduces intraoperative and postoperative bleeding to a minimum.